Equilibrium Orientation and Adsorption of an Ellipsoidal Janus Particle at a Fluid-Fluid Interface - Gunther, Florian; Xie, Qingguang; Harting, Jens (Colloids and Interfaces, 2020)
We investigate the equilibrium orientation and adsorption process of a single, ellipsoidal Janus particle at a fluid-fluid interface. The particle surface comprises equally sized parts that are hydrophobic or hydrophilic. We present free energy models to predict the equilibrium orientation and compare the theoretical predictions with lattice Boltzmann simulations. We find that the deformation of the fluid interface strongly influences the equilibrium orientation of the Janus ellipsoid. The adsorption process of the Janus ellipsoid can lead to different final orientations determined by the interplay of particle aspect ratio and particle wettablity contrast.
CRIS-Team WoS Importer:2021-01-08